Investigation of the Prevalance of Self-Medication with Antibiotics Among Students in Afganistan : Insight From Kabul Medical University - Maleena Safi; Nadi Saydi; Tamanna Quraishi (International Journal of Integrated Science and Technology, 2024)
Self-medication with antibiotics poses a significant public health challenge worldwide, contributing to antimicrobial resistance and adverse health outcomes. This cross-sectional study aimed to investigate the prevalence, patterns, and factors associated with self-medication among medical students at Kabul Medical University in 2021. A descriptive approach was employed, utilizing online questionnaires to collect data from a sample of 216 participants. Results revealed a high prevalence of self-medication, with 67.1% of students reporting antibiotic use in the past year and 56.2% engaging in self-medication during the same period. Sore throat emerged as the most commonly self-treated ailment, indicating a tendency to misuse antibiotics for minor symptoms. Reasons for self-medication included perceived symptom severity, previous experience, and the convenience of antibiotic use. Financial constraints and time limitations also influenced this behaviour. These findings underscore the urgent need for targeted interventions to promote responsible antibiotic use and mitigate the risks associated with self-medication. Educational campaigns, regulatory measures, and healthcare reforms are recommended to address the multifaceted drivers of self-medication. In conclusion, this study provides valuable insights into the prevalence and determinants of self-medication with antibiotics among medical students, highlighting the importance of public health initiatives in curbing inappropriate antibiotic use and safeguarding antimicrobial efficacy.